The role of livestock in organic nutrient management - Dijkman, J. (Ethiopian Society of Animal Production, 2000)
Rapid increases in population densities and the associated environmental changes have meant increased problems for farmers in planning effective resource management strategies. In response to these driving forces and to improve the efficiency of the use of the available nutrient resources many traditional systems of management will have to change. There are, however, many ways in which current systems of nutrient resource could be improved without the need for large investment. These may consist of an improvement in the use, collection and storage of manure and the optimized use of available biomass production. The implementation of this type of strategies, however, will depend on the utilization of methodologies that would enable both researchers and Development workers to approach the issues in a dynamic, integrated and system-oriented manner. Moreover, there is also a clear need to improve the delivery of research results to extension workers and their client-farmers, and particularly for materials and methodologies that reduce the complexity, of these interactions and which would allow farmers to take a more active part in the evaluation of alternative strategies.